Decision Making System Using Fuzzy Mamdani in Detecting Cholestrol Disease - Novita, Nanda; Anisa, Yuan; Zuhanda, Muhammad Khahfi; Eliska, Eliska; Widiantho, Yuri (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Cholestrol is a physical property of natural substances in the form of fat which is useful as an essential building material for the body for the synthesis of important substances such as cell membranes and insulation materials around nerve fibers. In addition, it is useful for sex hormones, kidney children and bile acids. High cholesterol levels or hypercholesterolemia in the blood triggers hypertension. This is because high cholesterol is the cause of blockages in peripheral blood vessels that reduce blood supply to the heart. Based on these studies, it shows that the influence of obesity (overweight) and blood pressure has a role in the risk of cholesterol disease. Based on the rule view, it can be seen that the cholesterol level is 210 or it can be said that it is in the alert category, it can be seen for blood pressure 100.6 and BMI 31.8.The fuzzy mamdani method is often also known as the min-max method. Where it uses min or minimum on the implication function and max or maximum on the composition between implication functions. In its application, the madani fuzzy method uses 4 stages, namely the formation of fuzzy sets, application of implication functions, rule composition, defuzzification. This research uses a simulation method of calculating cholesterol. This research analyzes using fuzzy mamdani and matlab software assistance.